IMPLEMENTASI PELAYANAN PENGUNJUNG DI LEMBAGA PEMASYARAKATAN KELAS IIB KOTA BLITAR - Sugeng Widodo (Universitas Kadiri, 2019)
This study discusses the reality of implementing visitor services in correctional institutions along with important factors that influence them. Through a qualitative approach with in-depth interviews, this study found that the implementation of visitor services was by the standard operating procedure (SOP), but there were still obstacles, namely limitation of the number of human resources available, especially to compensate for the number of overloaded prisoners.